How the corona pandemic affects the global fight against tuberculosis and how to react - Ulrichs, Timo (Frontiers in Cellular and Infection Microbiology, 2023)
The emergence of the acute pandemic by SARS-CoV-2 is a setback for the fight against chronic pandemics like tuberculosis (TB), malaria and HIV/AIDS. In fact, after more than a decade of decreasing fatality numbers, 2020 saw a re-increase of the number of people dying from TB. After covid-19, TB was the infectious disease with the second-highest fatality rate by an infectious disease caused by a single pathogen, namely 1.6 million deaths in 2021. It is expected by WHO, that the pandemic years to come and even after the pandemic will continue this trend. More efforts are needed to support TB control structures, namely as integral part of general health care system strengthening measures.